Here for the Hearing Analyzing the Music in Musical Theater - Buchler, Michael; Decker, Gregory John (Tracking Pop, 2023)
This book offers a series of essays that show the integrated role that musical structure (including harmony, melody, rhythm, meter, form, and musical association) plays in making sense of what transpires onstage in musicals. Written by a group of music analysts who care deeply about musical theater, this collection provides new understanding of how musicals are put together, how composers and lyricists structure words and music to complement one another, and how music helps us understand the human relationships and historical and social contexts. Using a wide range of musical examples, representing the history of musical theater from the 1920s to the present day, the book explores how music interacts with dramatic elements within individual shows and other pieces within and outside of the genre. These essays invite readers to consider issues that are fundamental both to our understanding of musical theater and to the multiple ways we engage with music.